2004
DOI: 10.1111/j.1945-5100.2004.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory hydration of condensed magnesiosilica smokes with implications for hydrated silicates in IDPs and comets

Abstract: Abstract-Samples of silica-rich and MgO-rich condensed, amorphous magnesiosilica smokes were hydrated to monitor systematic mineralogical and chemical changes as a function of time and temperature controlled by their unique metastable eutectic compositions, their porous texture, and the ultrafine, nanometer grain size of all entities. At water supersaturated conditions, proto-phyllosilicates formed by spinodal-type homogeneous nucleation. Their formation and subsequent growth was entirely determined by the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…However, traces of layer silicates were probably present in Halley dust (Rietmeijer et al 1989), minor amounts layer silicates are present in porous aggregate IDPs Rietmeijer and Mackinnon 1985a) and meteors with CI-like physical properties enter the Earth's atmosphere on comet-like orbits (Rietmeijer 2000) offering ample support that hydrated aggregate IDPs, cluster IDPs, and even larger aggregate debris is associated with cometary sources. Hydrocryogenic alteration in dirty-ice mixtures (Rietmeijer 1985(Rietmeijer , 2002a) and laboratory hydration experiments on amorphous MgSiO dust analogs (Rietmeijer et al 2004) provide a framework supporting the feasibility of dust hydration in cometary environments. The original subdivision of anhydrous and hydrated IDPs was based on the findings of an infrared study of 26 chondritic IDPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, traces of layer silicates were probably present in Halley dust (Rietmeijer et al 1989), minor amounts layer silicates are present in porous aggregate IDPs Rietmeijer and Mackinnon 1985a) and meteors with CI-like physical properties enter the Earth's atmosphere on comet-like orbits (Rietmeijer 2000) offering ample support that hydrated aggregate IDPs, cluster IDPs, and even larger aggregate debris is associated with cometary sources. Hydrocryogenic alteration in dirty-ice mixtures (Rietmeijer 1985(Rietmeijer , 2002a) and laboratory hydration experiments on amorphous MgSiO dust analogs (Rietmeijer et al 2004) provide a framework supporting the feasibility of dust hydration in cometary environments. The original subdivision of anhydrous and hydrated IDPs was based on the findings of an infrared study of 26 chondritic IDPs.…”
Section: Discussionmentioning
confidence: 99%
“…When water react with silicates in anhydrous IDP the extent of hydration will be a function of water/"rock" ratios, time and temperature of hydration as well as the ability of water to move through a porous medium. Laboratory hydration of a porous condensed MgSiO smoke demonstrated that porosity is indeed an important controlling factor during hydration (Rietmeijer et al 2004). The most likely outcome of the hydration process would be a continuous and gradual transition from anhydrous silicates (crystalline or amorphous) to partially and to fully-hydrated silicates among aggregate IDPs that can be from the same parent body or from different parent bodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vapor phase‐condensed amorphous magnesiosilica grains typically have distinct DME serpentine (Mg 3 Si 2 O 7 ) and smectite (Mg 6 Si 8 O 22 ) dehydroxylate compositions and a rare amorphous Mg 8 SiO 10 compound (Rietmeijer et al. , , , ). The absence of these nanograin compositions in the present study is consistent with the compactness of the original magnesiosilica smoke that allowed efficient chemical diffusion.…”
Section: Observationsmentioning
confidence: 99%
“…Periclase (MgO) due to brucite dehydration and DME amorphous Mg 8 SiO 10 grains (Rietmeijer et al. , ) reacting with iron melt could account for the low‐Si ferromagnesiosilica grains. Although Mg,Fe‐oxides (Fe/[Mg + Fe] <0.3) are very rare (Fig.…”
Section: Thermal Evolutionmentioning
confidence: 99%